Ecological stability of broad bean (Vicia faba L.) in organic farming conditions - N. A. Georgieva; V. I. Kosev (Вавиловский журнал генетики и селекции)
The main direction in the breeding of legumes is the development of high-productive cultivars with stable yields. In order to assess the ecological stability of 17 broad bean accessions (Fb 1896, Fb 1903, Fb 1929, Fb 2481, Fb 2486, Fb 3270, BGE 002106, BGE 029055, BGE 032012, BGE 041470, BGE 043776, BGE 046721, FbH 13, FbH 14, FbH 15, FbH 16, BGP) with regard to key quantitative traits, a field experiment was conducted in the Institute of Forage Crops (Pleven) in 2016–2018. Plants were grown under organic farming conditions without the use of fertilizers or pesticides. Three types of stability parameters were calculated based on regression, variance, and nonparametric analysis. The results of the variance analysis showed a significant genotype × environment interaction for all quantitative traits except pod width. The factor ‘environment’ had the greatest impact on the phenotypic manifestation of the traits, followed by the factors ‘genotype’ and ‘genotype × environment interaction’. In terms of plant height and 1st pod height, accessions FbH 16 and FbH 13 can be classified as high (79 cm, 35 cm) and ecologically stable (bi = 0.76, bi = 0.79). BGE 029055 was little variable and had high numbers of pods (15) and seeds (41) per plant. Accessions FbH 14, FbH 16, FbH 15, and BGP were distinguished by high seed weight per plant (from 28.36 to 34.93 g), but they exhibited instability (bi > 1) under unfavorable environmental conditions. In contrast, Fb 1903, BGE 043776, and Fb 3270 were very stable (bi < 1) but low-productive. Accessions Fb 1896, Fb 1929, Fb 2481, Fb 2486, BGE 002106, and BGE 029055 showed intermediate parameters, as they had the coefficient of linear regression close to 1, but they were also low-productive. BGE 041470 appeared to be of special interest for breeding. It had high values of 100 seed mass (101.38 g) and seed weight per plant (32.14 g), being relatively stable (bi = 1.10). GGE biplot analysis determined accessions BGE 046721, BGE 032012, FbH 15 and FbH 16 as a promising breeding material combining high and stable seed yield.